The success rate of interphase fluorescence in situ hybridization in plasma cell disorders can be improved using unconventional sources of plasma cells. (11th October 2021) - Panakkal, Vandana; Rana, Sonia; Rathore, Shailja; Anshu, Anshu; Balakrishnan, Anand; Singh, Charanpreet; Jandial, Aditya; Sachdeva, Man Updesh Singh; Varma, Neelam; Lad, Deepesh; Malhotra, Pankaj; Sreedharanunni, Sreejesh
Abstract: Background: Immunomagnetic cell sorting (IMCS) is a preferred technique for the enrichment of plasma cells (PC) before fluorescence in situ hybridization (FISH). Here, we share our real‐world experience regarding the success rate of IMCS, its limitations, and the utility of alternate sources to obtain a successful FISH in various PC disorders. Materials and Methods: A retrospective analysis was performed in patients with a PC neoplasm, who underwent bone marrow (BM) examination, and FISH testing over 30 months. In all cases with an unsuccessful IMCS, an attempt was made to identify the cause of failure. Results: Immunomagnetic cell sorting of PCs was successful in 395/450 cases (87.8%; 77/98 cases (78.6%) with <10% PCs and 318/352 (90.3%) with ≥10% PCs in BM aspirate; P = .003). Among cases with unsuccessful IMCS (<10% PCs; n = 21 and ≥10% PCs; n = 34), an alternate source could be used successfully in 34 (62%) patients and includes air‐dried trephine biopsy imprint smears (n = 28) with aggregates or sheets of PCs, fine‐needle aspiration smears/biopsy from plasmacytoma (n = 5), and ascitic fluid (n = 1). 284/395 (71.9%) patients with successful IMCS and all 34 cases with an alternate source of PCs showed at least one cytogenetic abnormality on four‐probe FISH. Conclusion: Variations in the sample quality together with significant variation in the number of PCs between BM aspirate and the trephine biopsy imprint smears/biopsy reduce the success rate of IMCS in a real‐world scenario and necessitate utilization of patient‐specific alternate sources of PCs like a trephine biopsy imprint or cytology smears from extramedullary sources for successful FISH testing in PC neoplasms.